A controlled recipient evacuation process to form composite profiles from flat multi-angle prepreg stacks – infrastructure and C-profile verification - E. Kappel (Taylor & Francis Group, 2019)
Single-diaphragm forming is a cost saving alternative to labor-intensive ply-by-ply layup. This paper reports on forming of flat uncured multi-angle prepreg stacks into C shape. The main focus is on the forming-process profile , which has attracted little attention in previous studies on the topic. Hexcel’s M21E/IMA prepreg is examined within the study to analyze the particular effect of the prepreg’s interleaf layers on the forming process and vice versa. Specimens with different multi-angle stackings were formed at 40, 60 and 80 °C, on male tools with 4, 6 and 8 mm radii. It is shown that the composed infrastructure setup allows for a precise control of the recipient pressure profile. The forming status is monitored based on a resistance-measurement-based approach, whose application suggests a two-phase forming process characteristic. Recipient pressure levels of 60 and 510 mbar below ambient pressure were identified as practical for gentle forming. It could be shown that interleaf layers of M21E/IMA specimens are not harmed considerably by the forming procedure. Overall, the proposed forming process led to prepreg preforms of adequate quality, suitable for series production.